Excess credit and the South Korean crisis - Panicos O. Demetriades; Bassam A. Fattouh (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
We provide a novel empirical analysis of the South Korean credit market that reveals large volumes of excess credit since the late 1970s, indicating that a sizeable proportion of total credit was being used to refinance unprofitable projects. Our findings are consistent with theoretical literature that suggests that soft budget constraints and over-borrowing were significant factors behind the Korean financial crisis of 1997-98.
Keywords: G18; O16; 330; over-borrowing; South Korea; financial crisis; Kreditmarkt; Südkorea; Finanzmarktkrise